ANALISIS MINIMNYA DOKUMENTASI KARYA SASTRA LAMPUNG: ANCAMAN BAGI EKSISTENSI WARISAN BUDAYA LAMPUNG - Mildawati, Arini; Kouri Asyiah; Rahmat Prayogi; Bambang Riadi (Yayasan Literasi Sains Indonesia, 2024)
This article aims to examine the factors that cause the lack of documentation of Lampung literary works to threaten the existence of Lampung's cultural heritage. This research uses descriptive qualitative research methods. Qualitative research is research that describes phenomena such as behavior, perception, motivation and behavior experienced by research subjects in the form of words and language, using various scientific methods. The aim of this research is to find out more about the factors and efforts that need to be taken to overcome the lack of documentation of Lampung literary works. The research results show that the factors causing the lack of documentation of Lampung's literary works are a lack of awareness of the importance of cultural preservation among society, a lack of facilities and resources for documenting literary works, globalization and the dominance of modern culture, and a lack of support from the government and related institutions. So the efforts that need to be made to preserve Lampung's cultural heritage are to work together to face the challenges of modernization so that local culture continues to exist for the next generation